THE CLASS STRUCTURE OF CONTEMPORARY LITHUANIA: A NEO-WEBERIAN ANALYSIS - Morkevičius, Vaidas; Norkus, Zenonas (Sociologija. Mintis ir veiksmas, 2012)
This article analyses social inequality and political processes in post-Communist Lithuania, using the neo-Weberian class theory of Robert Erikson, John Goldthorpe and Lucienne Portocarero (EGP). The opening section considers why the analysis of social structure, which was a central concern in classical sociology, has been so neglected in Lithuanian sociology since the restoration of independence. There are just two exceptions to this trend, discussed in the same section – Rūta Brazienė’s 2002 thesis and the 2005 volume edited by Arvydas Matulionis. The first part also compares inductive (data-driven) and deductive (theory-driven) methodologies of social structure analysis to substantiate the advantages of the latter for this article’s empirical analysis. The second part outlines EGP class theory, considered as a creative continuation of Weber’s classical analysis of social structure, and as a genuine alternative to Marx’s theory of classes and class struggle. EGP class theory is compared with two other approaches – Erik Olin Wright’s neo-Marxist class theory, which emphasises exploitation relations between classes, and American social stratification analysis, which focuses on the measurement of socio-economic status (SES). The third section offers a neo-Weberian examination of post-Communist Lithuania’s class structure, represented by four different EGP class types. Diachronic and synchronic comparisons and historical analysis are used to point out the features of Lithuanian class structure that are shared with other similar countries and those features that are nationally specific. To this end, data from Round 4 of the European Social Survey in Lithuania (conducted at the end of 2009) is used. In the last section, which applies statistical methods of correspondence analysis, a slightly modified EGP class model is used to explore manifestations of social inequality (conceived in Weberian terms as an unequal distribution of ‘life chances’), as well as the voting and ideological orientations of the Lithuanian electorate. Key words: Erikson-Goldthorpe-Portocarero (EGP) class theory,